Animal Models of Multiple Myeloma Bone Disease - Mehdi, Syed Hassan; Nafees, Sana; Mehdi, Syed Jafar; Morris, Carol A.; Mashouri, Ladan; Yoon, Donghoon (Frontiers in Genetics, 2021)
Multiple Myeloma (MM) is a clonal B-cell disorder characterized by the proliferation of malignant plasma cells (PC) in the bone marrow (BM), the presence of monoclonal serum immunoglobulin, and osteolytic lesions. It is the second most common hematological malignancy and considered an incurable disease despite significant treatment improvements. MM bone disease (MMBD) is defined as the presence of one or more osteolytic bone lesions or diffused osteoporosis with compression fracture attributable to the underlying clonal PC disorder. MMBD causes severe morbidity and increases mortality. Cumulative evidence shows that the interaction of MM cells and bone microenvironment plays a significant role in MM progression, suggesting that these interactions may be good targets for therapy. MM animal models have been developed and studied in various aspects of MM tumorigenesis. Particulary, MMBD has been studied in various models and each model has unique features. Since the general features of MM animal models have been reviewed elsewhere. The current review will focus on the features on MMBD animal models.